An overview of development processes and farmers' interactions in a participatory forest fire prevention programme in Jambi province, Indonesia - Otsuka, M.; Sumantri; Hariri, D.; Yunardi, S. (Center for International Forestry Research, 2001)
The participatory forest fire prevention programme of Forest Fire Prevention Management Project (FFPMP) aims at intensive fuel management and fire control with the integrated green belt on community land on the boundary of Berbak National Park, Jambi Province, Sumatra. It aims to motivate farmers to cultivate their land continuously, reducing fire hazards and risks through formation of fuel breaks around the forest. Participating farmers face technical limitations in seedling production, land preparation without burning, and crop planting and protection. They cannot easily perceive benefits of the green belt with line planting of the small number of trees. Land-oriented farmers experienced in growing crops and constructing facilities are more advantaged than local farmers dependent on forest resources. Current socio-economic conditions have accelerated diverse programme evolution with farmers’ different responses. FFPMP has funded materials and facilities to substitute for farmers’ lack of technical and economic capabilities. It may also modify the programme to optimise farmer participation and facilitate effective fuel break formation, including flexible design of planting sites along the green belt with various crops, new land preparation technologies, establishment of pilot small-scale nurseries, and strengthening of community organisations for less advanced farmers. This paper addresses the socio-economic sustainability of the participatory green belt programme.